SMART PAGE TURNER - ARCHANA, B.; SATHISH, K.; RAM, B.SURESH; SREE, K.KAVYA; LAXMI, T.BHAGYA (The journal of contemporary issues in business and government, 2021)
The Aim of this project is to make reading comfortable for people without hands. Page turner has been designed, allowing a user to turn a page of printed matter by simply touching a switch with leg. Our model is effectively used to people who could not move their hands and wish to read books